PENGEMBANGAN TEKTONIKA FASHION ARCHITECTURE MANTEL - Denny Husin; Fermanto Lianto (Jurnal Bakti Masyarakat Indonesia, 2020)
Market competition and the demands of the Indonesian fashion world, encourage the tailors of Kampung Baru to involve educational institutions to provide new academic and technical insights on fashion architecture in order to increase the usability and product image that results. Therefore a study was arranged to stimulate the participation of new village tailors to produce fashion architecture tectonics on coat designs. This knowledge can open up a new horizon of tailors in seeing clothing as a form of space. Using research techniques in community engagement activities has the potential to insert experiments in daily activities of the community by increasing the knowledge and skills of tailors. This research is a qualitative research with an action research approach, developing knowledge based on specific problems in the form of the ability of new village tailors who are stagnant in the replication of conventional techniques. The moulage technique in fashion is combined with the collage technique in the field of architecture to produce a three-dimensional volume on the coat that is the mainstay of the collection. The two techniques are combined with loosely bounded details, combining hand and machine creations so that clothing can respond to body movements. The end result is a fashion with volumetric character, built on integrated layers while showing flexibility and fluidity when the wearer moves. Architectural knowledge in this study is not implemented as conventional science but is a modification of the spatial in the form of clothing. Although the final prototype is in physical form of clothing; the concepts, methods and development of tectonics combine two sciences, namely fashion architecture. The strength of the tailor is focused on the seams of the layers of clothing that make up the spatial volume and detail of the design so that it is recognized as a characteristicABSTRAK:Kompetisi pasar dan tuntutan dunia mode Indonesia, mendorong penjahit Kampung Baru untuk melibatkan institusi pendidikan untuk memberikan wawasan akademik dan teknik baru pada fashion architecture agar dapat meningkatkan nilai guna dan citra produk yang hasilkan. Maka dari itu sebuah penelitian disusun untuk menstimulasi partisipasi penjahit kampung baru untuk menghasilkan tektonika fashion architecture pada desain mantel. Pengetahuan ini dapat membuka cakrawala baru kelompok penjahit dalam melihat pakaian sebagai salah satu bentuk keruangan. Menggunakan teknik penelitian dalam kegiatan pengabdian kepada masyarakat berpotensi menyisipkan percobaan pada kegiatan harian masyarakat dengan meningkatkan wawasan dan keterampilan penjahit. Penelitian ini merupakan penelitian kualitatif dengan pendekatan action research, mengembangkan pengetahuan berdasarkan masalah spesifik berupa kemampuan penjahit kampung baru yang stagnan pada replikasi teknik konvensional. Teknik moulage pada fashion dikombinasikan dengan teknik collage di bidang arsitektur untuk menghasilkan volume tiga dimensional pada mantel yang menjadi andalan koleksi. Kedua teknik disatukan dengan detail loosely bounded, mengkombinasikan kreasi tangan dan mesin agar pakaian dapat merespon pergerakan tubuh. Hasil akhir berupa fashion yang berkarakter volumetrik, dibangun atas layer-layer yang terintegrasi sementara menunjukkan fleksibilitas dan fluiditas saat pemakainya bergerak. Pengetahuan arsitektur pada penelitian ini tidak diimplementasikan sebagai ilmu konvensional namun modifikasi keruangan dalam bentuk pakaian. Meskipun prototipe akhir berbentuk fisik pakaian; konsep, metode, dan pengembangan tektonika mengkombinasi dua keilmuan yakni fashion architecture. Kekuatan penjahit difokuskan pada jahitan terhadap lapisan pakaian yang membentuk volume keruangan dan detail pada desain sehingga dikenali sebagai ciri khas.